KINERJA LINGKUNGAN, KEPEMILIKAN MANAJERIAL TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Anggi Perdana; Rama Amdanir; Azman Khan (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to examine the influence of environmental performance and managerial ownership on corporate social responsibility (CSR) in LQ45 companies listed on the Indonesia Stock Exchange in 2019–2023. The research method used is a quantitative approach with multiple linear regression analysis techniques using secondary data obtained from company annual reports. The results show that managerial ownership has a negative and significant effect on CSR disclosure, while environmental performance has no significant effect on CSR. The conclusion of this study is that managerial involvement as shareholders can actually reduce the level of CSR disclosure, and the limited number of LQ45 companies that consistently disclose environmental performance in their annual reports. Keywords: Environmental Performance, Managerial Ownership, Corporate Social Responsibility, LQ45 Companies